Work Conditions and Problems of Former Care Workers After Returned to Indonesia - Nofrelia, Eldwita (Journal of Strategic and Global Studies, 2022)
Based on Indonesian-Japan Economic Partnership Agreement (IJEPA), Indonesia sends some nurses (perawat) who would be employed either as hospital nurses (perawat rumah sakit) or as care workers for the elderly (perawat lansia). Nurses who work in Japanese hospitals are required to meet Japanese nursing standards, through a competency test of Japanese nursing standards. This article discusses how Indonesian care workers adapt to working conditions while being in Japan and about the problem of nurses with Indonesian qualifications working with Japanese competency standards. This study is qualitative research using a survey method. The data collection technique used in this study was a questionnaire via google form. This study uses the theory of liminality to explain the adaptation process and the problems faced by Indonesian care workers in Japan. This study found out that there was a gap between what had been expected and what had been faced by Indonesian nurses (especially who were originally medical nurses) working in Japan, so that the “care workers” chose to return home and started to build a career in Indonesia.